INFORMATIKA SABAQLARÍNDA OQÍWSHÍLARDÍŃ BILIMLERIN BAHALAW FORMALARÍ HÁM USÍLLARÍ - Turmanov, Q.A. (SCIENCE and SOCIETY, 2023)
This article provides information on the forms and methods of assessing students' knowledge in computer science and ICT(information and communication technology) lessons. There are also instructions and recommendations on several types of assessment of knowledge and skills of students and the procedures for their implementation.
Keywords: assessment; assessment system; formative assessment; summative assessment; formal assessment; informal assessment; current control; thematic control; intermediate control; final control